We are everywhere : protest, power, and pride in the history of Queer Liberation - Riemer, Matthew, 1982-; Brown, Leighton, 1978- (California : Ten Speed Press, 2019)
"Have pride in history. Through the lenses of protest, power, and pride, We Are Everywhere is an essential overview -- and a visual record -- of the history of the Queer Liberation Movement in the United States. With exhaustively researched narrative and hundreds of stunning photographs, this sweeping book traces queer activism from its roots in the late-nineteenth-century -- long before the pivotal Stonewall Riots of 1969 -- to today, casting new light on many of the movement's trailblazing activists and organizations. Including images from more than seventy photographers and twenty archives, this inclusive and intersectional collection brings the queer past to life, allowing you to have pride in history while serving as a vivid reminder that none of us is free until all of us are free."-- back cover.
Introduction: Seeing queer history -- A century of subtle attack, 1867-1968 -- Freaking fag revolutionaries, 1968-1973 -- Sissy, the closet done burned down! 1973-1979 -- Fighting for our lives, 1980-1994 -- Conclusion: Until next time.
Includes bibliographical references and index.
Keywords: Gays -- United States -- History; Gays -- United States -- Pictorial works; Sexual minority community -- United States -- History; Lesbians -- United States -- History; Transgender people -- United States -- History; Homophobia -- United States -- History